2016
DOI: 10.1098/rspb.2016.1634
|View full text |Cite
|
Sign up to set email alerts
|

The value of trophic interactions for ecosystem function: dung beetle communities influence seed burial and seedling recruitment in tropical forests

Abstract: Anthropogenic activities are causing species extinctions, raising concerns about the consequences of changing biological communities for ecosystem functioning. To address this, we investigated how dung beetle communities influence seed burial and seedling recruitment in the Brazilian Amazon. First, we conducted a burial and retrieval experiment using seed mimics. We found that dung beetle biomass had a stronger positive effect on the burial of large than small beads, suggesting that anthropogenic reductions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 60 publications
3
59
0
3
Order By: Relevance
“…The direct interaction between beetles and seeds, be it the secondary dispersal of defecated seeds or be it the movement of seeds in the seed bank, entails the relocation of seeds to microsites where conditions are different, which in turn changes the seeds' fate paths. Whether these new conditions affect plants positively or negatively, is species and context dependent, and may also vary according to the plant's developmental phase (Andresen & Levey, ; Culot et al., ; Griffiths et al., ). Further, dung beetle activity is likely to affect plants not only directly through seed relocation, but also indirectly by creating some of those new conditions encountered by either the relocated seed, or by an already established seedling (e.g., increased nutrient accessibility for plant uptake; Santos‐Heredia et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct interaction between beetles and seeds, be it the secondary dispersal of defecated seeds or be it the movement of seeds in the seed bank, entails the relocation of seeds to microsites where conditions are different, which in turn changes the seeds' fate paths. Whether these new conditions affect plants positively or negatively, is species and context dependent, and may also vary according to the plant's developmental phase (Andresen & Levey, ; Culot et al., ; Griffiths et al., ). Further, dung beetle activity is likely to affect plants not only directly through seed relocation, but also indirectly by creating some of those new conditions encountered by either the relocated seed, or by an already established seedling (e.g., increased nutrient accessibility for plant uptake; Santos‐Heredia et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Many important ecological functions are derived from this behavior (Nichols et al., ; Santos‐Heredia & Andresen, ; Santos‐Heredia et al., ), including the accidental movement of seeds, either when seeds in feces are buried (i.e., vertical secondary seed dispersal; Andresen & Feer, ), or when seeds already buried in the soil are moved along their tunnels (Pouvelle, Jouard, Feer, Tully, & Ponge, ). Secondary seed dispersal by tropical dung beetles has been the focus of numerous studies (e.g., Andresen & Feer, ; Culot, Huynen, & Heymann, ; Culot, Mann, Muñoz‐ Lazo, Huynen, & Heymann, ; Griffiths, Bardgett, Louzada, & Barlow, ; Lawson, Mann, & Lewis, ; Shepherd & Chapman, ). On the other hand, the vertical re‐distribution (i.e., upward and downward movement along the vertical axis) of seeds already buried in the soil has been proposed (Pouvelle et al., ), and quantified in one study, but only for seed exhumation, that is, when buried seeds are brought back to the surface (Santos‐Heredia & Andresen, ).…”
mentioning
confidence: 99%
“…seed dispersal) 2022 . For example, seed predation by both vertebrates and invertebrates 23,24 can limit germination and subsequent recruitment 22 . Long-term experiments have demonstrated the impact of vertebrates on recruitment, showing how this group contributes to the maintenance of tropical forest species and structural diversity 2528 .…”
Section: Introductionmentioning
confidence: 99%
“…Dung beetle activity can favour seed dispersal in different ways: seeds can be transported in a more suitable microclimate (Shepherd & Chapman, ; Andresen & Levey, ; Griffiths et al ., , ), they can be protected by predators and pathogens (Shepherd & Chapman, ; Feer, ), and they can benefit from a reduction in clumping with lower competition and density‐dependent mortality (Andresen & Feer, ; Lawson et al ., ). Affecting seed survival in these ways, dung beetle activity could have important impacts upon plant regeneration and community composition (Griffith et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that provisioning of ecological functions by dung beetles may vary depending on species assemblage attributes and species identity (Bang et al, 2005;O'Hea et al, 2010;Beynon et al, 2012;Nervo et al 2016;Piccini et al, 2017). Abundance and biomass of dung beetle communities are pivotal factors that have been shown to be relevant for ecosystem functioning (Tixier et al, 2015;Griffiths et al, 2016). Large-bodied species have been found to provide a greater amount of ecological functions (Kaartinen et al, 2013;Nervo et al, 2014), even more so at higher abundance (Braga et al, 2013;Ortega-Martínez et al, 2016), but at the same time they are sensitive to ecological stressors (Larsen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%